Deteksi Financial Statement Fraud : Model Beneish M-Score, dan Model F-Score - Patmawati, Patmawati; Rahmawati, Meita (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p03, 2023)
The research aims to find out which model is most effective in detecting financial statement fraud by using the Beneish M-Score model and the F-Score model. The research population of the banking sector is listed on the Indonesia Stock Exchange for the period 2018 - 2020 with a total of 48 banks. The research sample totaled 40 banks using a purposive sampling method. The results of the study stated that by calculating the index using the beneficial M-Score model, it showed that there were indications of banks committing financial statement fraud in 2018 at 2.5%, in 2019 at 95% and in 2020 at 97.5%. Meanwhile, using the F-Score model in 2018 it was 5%, in 2019 it was 7.5% and in 2020 it was 5%. Based on these two models, an effective model for detecting financial statement fraud is the Beneish M-Score model. Keywords: Financial Statement Fraud; Model Beneish M-Score; Model F-Score.